Sustainability in the Oil and Gas Sector Adaptation and Mitigation Strategies for Tackling Climate Change - Walker, Thomas; Barabanov, Sergey; Michaeli, Maya; Kelly, Victoria (Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2024)
XIX, 225 p. 46 illus., 43 illus. in color.